"Nasceste da divisão e ela te divide mais": análise do discurso religioso de membros de ramificações da Assembléia de Deus no Brasil e em Portugal. - Silva, Dalexon Sérgio da (2019)
In this thesis, we analyze the religious discourse of members of branches of the Evangelical Church Assembly of God in Brazil and Portugal. Today, it is the largest evangelical church in these two countries. It originated, with less than twenty members, on June 18, 1911, in Belém do Pará, by a division of this dissident group of the Baptist Church, in adherence to the Pentecostal message preached by two Swedish missionaries: Gunnar Vingren and Daniel Berg. Today, according to the Brazilian Census of 2010, this church is present in the whole Brazilian territory, with 12,314,410 members. It also presents itself in Portugal, through various ramifications in ministries. Because of its expressive social representation, with subjects inserted, in important segments of these countries, it is important to analyze it, in the production of its symbolic object, the assembly discourse. To this end, research questions were mobilized. Thus, we investigate from which position-subject each member of these ramifications in Brazil and in Portugalenunciates and discursive formations generated from the ramifications of the Precursor Church. We also aim to investigate the effects of meaning produced from what is common and different between the members of these branches in these countries and the discursive modalities of subjective functioning, comparing the process of identification, counter-identification and disidentification of these subjects interviewed in relation to the Precursor Discursive Formation (DF) of congregational believer. In this guideline, we analyze the religious discourse of four subjects belonging to two congregational branches in Brazil and four subjects belonging to two congregational branches present in Portugal, making a total of eight subjects interviewed. Later, the interviews were transcribed and analyzed by the bias of the Discourse Analysis of the French Pheheutian Line (DA). The analyses also dialogue with authors of the Sciences of Religion and point to the emergence of a heterogeneous congregationism, which subverts the perception of the Assembly of God, as inscribed in classical Pentecostalism. Also, in dialogue, in an interface with authors of Cultural Studies, we propose that the Assembly identity does not appear to be fixed anymore. However, it is currently present in three ways: desiring fixed identity, disjointed assembly identity and heterogeneous assembly identity. Finally, the research shows that the ones from the Assembly of Godof the Pernambuco Convention (Recife) were themost identified with the knowledge inscribed in the DF of the first congregational believers.